The Effect of Salt and the Addition of Several Acid Types on the Quality of Bottled Green Pepper During Storage - Endah Djubaedah; Djumarman .; Enny Hawani Lubis; Tuty Hendraswaty (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2004)
Research on the effect of salt and the acid types addition on the quality of bottled green pepper during storage has been conducted. Treatments were used 10 % and 20 % of salt, 0.2 % of citric acid and 4 % of acetic acid. The product were stored for 3 months and were analyzed for green color degree, pH, total plate count (TPC), piperine and total solid content. The results showed that citric acid treatment, better than acetic acid treatment, indicated by higher degree of green color (5.30 – 5.92) and pH 4.5 – 4.7 while the other 4.46 – 4.60 of green color degree and pH 3.5 – 3.9. Treatment of 20 % salt was more effective than 10 % of salt in preventing microorganism growth which was indicated by lower TPC value (2 – 5 colony/g). Products treated by citric acid and acetic acid also had lower TPC value, 3 – 5 colony/g and 2 – 3 colony/g respectively. Combinations of salt and acid treatments gave significant effect on it. Piperine content were relatively unchanged during 2 months storage (6.5 - 8 %) but it decreased in 3 months storage (5 – 6 %). The best quality was product treated by 20 % of salt and 0.2 % of citric acid. It was also treated by soaking in 2 % of Na2CO3 for 30 minutes, blanching for 5 minutes, addition of 300 ppm SO2 and heating in 100 °C for 15 minutes as constant treatment. The product was also feasible financially on capacity 1,000 bottle per day. Selling Rp. 4,000.00 per bottle will give benefit Rp. 60,000,000.00 per 6 months with 1.11 benefit cost ratio (B/C). Key words : Green pepper, pickle, spices, bottled green pepper.